2003
DOI: 10.1002/mde.1099
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of the use of student evaluations: implications for universities

Abstract: In this paper, we develop an analytical model of joint maximizing behavior on the part of students and professors to develop policy rules for universities who use student evaluations as tools for increasing professor effort and, thereby, student knowledge. More precisely, we examine the potential benefits of student evaluations, the consequences of over-emphasizing them and the optimal level of emphasis that should be placed on them. This exercise allows us to determine conditions under which student evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Another survey that is used widely to measure the quality of the teaching process from the students' opinions is the “student evaluations of teaching (SETs)” (Bastick, 2001, pp. 1‐2), which is used widely in the US as a part of the QA cycle to help in decisions about the promotion, the payment and the tenure of the teachers (Kanagaretnam et al , 2003, p. 1).…”
Section: The Categories Of the Modelmentioning
confidence: 99%
“…Another survey that is used widely to measure the quality of the teaching process from the students' opinions is the “student evaluations of teaching (SETs)” (Bastick, 2001, pp. 1‐2), which is used widely in the US as a part of the QA cycle to help in decisions about the promotion, the payment and the tenure of the teachers (Kanagaretnam et al , 2003, p. 1).…”
Section: The Categories Of the Modelmentioning
confidence: 99%
“…Further, they note that SEIs should be designed to capture data on course materials and curriculum design/course development and other relevant dimensions of effective teaching. In defense of SEIs , Kanagaretnam et al (2003), showed that the use of student evaluations in the assessment of professors "had a positive impact as they had the potential to improve the professor effort and consequently the acquired knowledge of students. "…”
Section: Methodology Criticismsmentioning
confidence: 99%
“…Economists have thoroughly characterized the dynamics between professors, disciplines, and institutions that contribute to grade inflation at this level (Sabot & Wakeman-Linn, 1991;Yip & Yang 2003;Chan, Hao, & Suen, 2007). The role of student evaluations of professors has been highlighted as a major contributor to grade inflation (Kanagaretnam, Mathieu, & Thevaranjan, 2003). However, much less attention has been given to grade inflation at lower levels.…”
Section: P Walshmentioning
confidence: 99%